(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
This article explores the development of market-oriented agricultural holdings in the European Union (EU), with a specific focus on the Bulgarian agricultural sector. By analyzing agricultural holdings within the Farm Accountancy Data Network (FADN), the study aims to focus the challenges and opportunities faced by farmers in a market-driven agricultural landscape.; The EU's Common Agricultural Policy (CAP) has been instrumental in shaping the agriculture sector across member states. As the EU transitions towards a more market-oriented approach, agricultural holdings are required to adapt to changing market dynamics, technological advancements, and environmental sustainability. Hence these are the holdings which could deploy in practice the Agriculture 4.0 techniques.Through a comprehensive analysis of the FADN data, this article aims to identify the factors that contribute to the success or failure of market-oriented agricultural holdings in Bulgaria.; The Bulgarian case study provides insights into the challenges faced by market-oriented agricultural holdings. The country's unique socio-economic characteristics, including a rural population and a history of agricultural production, make it an interesting case for analysis. The study examines key indicators such as farm size, land use, production diversity, and income levels within the FADN database. Furthermore, it explores the impact of EU policies, market integration, and access to financial resources on the development of these holdings.